Environmental impacts assessment of water resources projects : concerns, policy issues, perceptions, and scientific analysis - Goel, R. S. (Series on management of water, power, and environmental resources, 2000)
In the Indian context; papers presented at the National Workshop on Assessment and Management of Environment Impacts in Hydropower and River Valley Projects, held on 9-12 May, 2000, at Hotel Samrat, New Delhi, India.